Implementación de un sistema de comunicación con telefonía en el hotel higuerón de la Espam. - Chávez Roca, José Andrés (2014)
In order to improve the flow of information between departments a communication system based on IP phones in the Fig Tree Hotel ESPAM MFL was implemented. Which consists of a local area network with 14 points for cable internet connection 9 to Access Point connection via WIFI and 19 IP phones for communication between departments? For the execution of the implementation work was done with the method of development of free Hardware for the development and implementation of the network and IP telephony equipment, which was of great import to gather information to determine the strategic location of the equipment used, settings and check for proper operation. Finally was verified by testing the communication system improved the flow of information between departments Hotel, both the network connections for internet access, IP telephone communication as working properly.